Fiscal Transfers and Community Economic Welfare: Evidence from Murung District - Sari Damayanti; Sunaryo N. Tuah; Benius (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
Indonesia’s fiscal decentralization provides village funds and tax revenue sharing funds to strengthen village autonomy, support public services, and enhance community economic welfare. This study examines the impact of village fund allocation, village fund, and tax revenue sharing funds on the economic welfare of communities across 13 villages in Murung District, Murung Raya Regency, from 2020 to 2024. Using a quantitative explanatory approach, the research applies descriptive and inferential statistical methods, including validity and reliability tests, multiple linear regression, and significance testing. The findings reveal that fund allocation, village fund, and tax revenue sharing funds significantly influence key indicators of economic welfare, such as household income, access to clean water, and the growth of active micro-enterprises. Among these, village funds emerge as the most dominant variable, contributing directly to economic participation and service access. The regression model demonstrates strong predictive power. These results align with theories of fiscal decentralization, public finance allocation, and welfare economics emphasizing the role of targeted fiscal transfers in reducing inequality and enhancing local development. The study recommends optimizing sharing funds for productive programs, integrating fiscal planning with SDGs and performance indicators, and strengthening governance, transparency, and community participation.